Perancangan Produk Kep Potong Rambut Dengan Mempertimbangkan Voice Of Customer Menggunakan Metode Quality Function Deployment - Irfan Sulistiawan; Heribertus Budi Santoso; Ana Komari (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2018)
In improving service to consumers by conducting research to find out Voice of Customer as a basis for further development planning using the Quality Function Deployment method. The development carried out is a haircut that has a function in accordance with customer expectations on the barbershop. The purpose of this study was to determine customer needs for hair cut kep products and priorities for the design and development of kep products that will be carried out. In this study a sample of 24 people was used, which carried out the interview method and the filling of closed questionnaires to find out what needs were met as a step for product development. From the results of data processing, the highest priority with a value of 23% in the technical response is the addition of functions to the haircut to increase comfort for the user and with the highest relative weight of 13% with the density attribute on the neck as one of the highest expectations of the user. Dalam meningkatkan pelayanan terhadap konsumen dengan melakukan penelitian untuk mengetahui Voice Of Customer sebagai dasar untuk perencanaan pengembangan yang lebih lanjut menggunakan metode Quality Function Deployment. Tujuan penelitian ini untuk mengetahui kebutuhan pelanggan terhadap produk kep potong rambut serta prioritas perancangan dan pengembangan produk kep yang akan dilakukan. Dari hasil pengolahan data didapat prioritas terbesar dengan nilai 23% pada technical respon yaitu penambahan fungsi pada kep potong rambut untuk menambah kenyamanan bagi pengguna dan dengan relative weight tertinggi 13% dengan atribut kerapatan pada bagian leher sebagai salah satu harapan tertinggi dari pengguna.